2022
DOI: 10.30650/ajte.v4i1.3208
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Difficulties in Translating Idiomatic Expressions: What and Why?

Abstract: This study analyzed students’ difficulties in translating idiomatic expression sentences at the sixth semester of English department of IAIN Langsa. It further discussed factors that trigger the problems. The research applied qualitative content analysis approach and the subject was 10 students of the sixth-semester of English education department, IAIN Langsa. Data collecting techniques were tests and interviews. The findings showed that the learners experienced several difficulties in translating idiomatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Some students tend to focus on the lexical meaning and ignore the grammatical meaning, so they do not realize that some nouns in Vietnamese did not have equivalent terms in English. The results are very much aligned with many authors as mentioned above such as Hastuti et al (2020) in terms of linguistic factors, Idami et al (2022) in terms of fixed expressions, Noviyanti (2020) when talking about both linguistic and nonlinguistic factors causing translation difficulties, Cuc (2018) in terms of syntax and lexical choices, and Phan et al (2021) in terms of cultural aspects and long structures causing translation difficulties.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some students tend to focus on the lexical meaning and ignore the grammatical meaning, so they do not realize that some nouns in Vietnamese did not have equivalent terms in English. The results are very much aligned with many authors as mentioned above such as Hastuti et al (2020) in terms of linguistic factors, Idami et al (2022) in terms of fixed expressions, Noviyanti (2020) when talking about both linguistic and nonlinguistic factors causing translation difficulties, Cuc (2018) in terms of syntax and lexical choices, and Phan et al (2021) in terms of cultural aspects and long structures causing translation difficulties.…”
Section: Discussionsupporting
confidence: 87%
“…Then, based on such difficulties, they have proposed some suitable solutions to soften the translation problems. Idami, Wati, and Balqis (2022) found that most of the Indonesian participants in their study underwent many difficulties when they were asked to translate idiomatic expressions because they encountered lexical knowledge, cultural differences, and different written styles in the source and the target language. They were unable to seek equivalence between the languages to locate intended meaning of the idiomatic expressions.…”
Section: Related Studiesmentioning
confidence: 99%
“…There are several difficulties faced by translators when translating idioms, namely: (1) idioms may not have an appropriate equivalent in TL, (2) idioms may have parts that are similar to TL, but the context of their use is different, (3) idioms can be used literally and idiomatically simultaneously, and (4) different idiom usage in both SL and TL (Baker, 2018;Ali & Sayyiyed, 2017;Idami, Wati, & Balqis, 2022). This issue may be observed in a number of idiomatic usages in daily life, such as the researchers" discovery of the variety show "GOING SEVENTEEN".…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that most translators struggle with translating idioms due to a variety of factors, including a lack of understanding of the grammatical structure of the target language (Utami, 2017), inability to find a target language equivalent (Mulyani and Ardiansyah, 2020), lack of knowledge of idiomatic expression, cultural differences between English and Indonesian, the difficulty in interpreting idiomatic expressions (Idami, Wati, and Balqis 2022), poor linguistic and pragmatic level of the target language, and the absence of strategy knowledge among the students in translating idioms (Al Mubarak, 2017). Lack of equivalent between the source and the target language leads to the problem in interpreting the meaning of the idioms such as the idiom "berkecil hati" in Indonesian cannot be found in the equivalent idiom in English rather than by translating with a similar meaning "scared" (Isodarus, 2018).…”
Section: Introductionmentioning
confidence: 99%